French infant total diet study: Dietary exposure to heat-induced compounds (acrylamide, furan and polycyclic aromatic hydrocarbons) and associated health risks. (August 2019) - Sirot, Véronique; Rivière, Gilles; Leconte, Stéphane; Vin, Karine; Traore, Thiema; Jean, Julien; Carne, Géraldine; Gorecki, Sébastien; Veyrand, Bruno; Marchand, Philippe; Le Bizec, Bruno; Jean-Pierre, Cravedi; et al.
Abstract: A total diet study (TDS) was conducted between 2010 and 2016 to assess the risk associated with chemicals in food of non-breast-fed children from 1 to 36 months living in France. Food samples were collected, prepared "as consumed", and analyzed for chemicals of public health interest. Acrylamide, furan and polycyclic aromatic hydrocarbons (PAHs) were analyzed as heat-induced compounds produced mainly during thermal processing of foods. Dietary exposure was assessed for 705 representative children using food consumptions recorded through a 3-consecutive-days record. As all calculated margins of exposure (MOE) for PAHs exceeded 10 000, dietary exposure of the infant and toddler population was deemed tolerable with regard to the carcinogenic risk. Conversely, the exposure levels to acrylamide and furan were considered as of concern, requiring management measures to reduce the exposure essentially by reducing the formation of heat-induced compounds during food production or preparation processes. Efforts should mainly focus on major contributors to the exposure, i.e. sweet and savoury biscuits and bars, and potatoes and potato products for acrylamide, baby jars of vegetables, with or without meat or fish for acrylamide and furan. Highlights: A total diet study was conducted in 2010-2016 to assess the dietary risk for young children associated with chemicals. The targeted population was non breastfed children under 3 years of age living in France. Heat-generated compounds were analyzed in composite food samples prepared "as consumed". For acrylamide and furan, the exposure levels were of concern, whereas for PAHs the risk was deemed tolerable. Efforts should continue to understand the origin of the contamination and further reduce the exposures.